DEVELOPMENT OF ENZYME IMMUNOASSAY AND ITS ROLE IN REPRODUCTIVE ENDOCRINOLOGY - Khan, Mir Hassan; Qureshi, M. Subhan (Journal of Ayub Medical College Abbottabad, 1993)
Radioimmunoassay is a powerful technique developed in 1960 by Solomon Berson and Rosalyn Yallow, who first devised a R1A for the measurement of insulin concentration in plasma1. The technique was far more sensitive and specific than any method existed at the time. RIA is used to analyse many biological substances that are present in minute amounts, including steroids, cyclic nucleotides, peptide hormones, viruses, bacterial antigen, enzymes, prostaglandins and drugs. Inspite of certain advantages of RIA in terms of sensitivity, specificity and wide applicability2, it has a number of disadvantages including high capital cost, as the devises used are very expensive and their maintenance in developing countries is extremely difficult task. Beside radiation hazards are a constant threat to personnel working in RIA laboratory. Decomposition of radiolabeled proteins upon storage is also a serious problem in RIA, affecting the sensitivity and reproducibility of assay system.